Membangun Sikap Disiplin Melalui Pembelajaran Seni Budaya pada Materi Seni Musik - Yuli Astuti; Samsuri Samsuri (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to shape the disciplinary character of students in elementary schools through music theory material with sub-materials of values ​​and forms of notation. The research method used is a descriptive qualitative method with data collection techniques of observation, questionnaires and interviews. The research was conducted in 7 (seven) meetings, the results of the research showed that there was a change in the theoretical understanding category with a percentage of 97.8%, and statements of disciplinary attitudes increased with a percentage of 95%. Disciplinary character is assessed based on the student's ability to sing the song Pada Mu Negeri according to the tempo, beats, and other punctuation marks contained in the score. The results showed that students were able to sing the song according to the punctuation marks in the sheet music.